Contraste entre propriedades optoeletrônicas em estruturas de tunelamento ressonante n-i-n baseadas em GaAs - Oliveira, Edson Rafael Cardozo de (2019)
Resonant Tunneling Diodes (RTDs) are semiconductor devices usually composed of two barrier structures embedding a single quantum well (QW) and highly doped layers in its extremities. Under an applied bias voltage, the charge carriers‘ energy aligns with the QW bound state and they can tunnel resonantly through the double barrier with, ideally, unity transmission probability and a peak in the current density for a certain voltage value is observed. This process occurs until the charge carriers‘ energy passes the energy of the QW bound state and now a sharp decline of the current density emerges due to the energetic misalignment of the charge carriers‘ energy and the QW bound state. The reduction of the current density at higher bias voltages leads to a region of Negative Differential Resistance, which for instance is utilized in high frequency RTD applications. Another essential property of RTDs is the peak-to-valley current ratio, which determines the device quality. It was demonstrated that the insertion of a pre-well adjacent to the emitter barrier enhances the PVCR through 2D-2D tunneling between pre-well and QW quantized states. Resonant Tunneling Diodes can also emit light. Accelerated electrons can experience collisions with other electrons, bringing them to the conduction band and generating holes at the valence band. Generated holes eventually recombine with electrons, thus, emitting light. This process is denominated electroluminescence through impact ionization. The electroluminescence combined with the unique RTDs properties, such as the NDR region and high frequency operation, enables the development of high speed functional opto-electronic devices, e.g., optical switches, logic gates, etc. In this work we study two resonant tunneling structures based on GaAs/AlGaAs with and without the presence of an InGaAs potential prewell and quantum well, using mainly transport and electroluminescence techniques. The main goal is to contrast the electroluminescent and transport properties in the study of charge carrier dynamics in these structures, and also, to compare the optoelectronic properties which the prewell addition provides. First, it is identified two independent impact ionization channels associated with the coherent resonant tunneling current and the incoherent valley current. Furthermore, by simulating a resistance variation for the I-V and the EL we observe the possibility to tune the EL on-off ratio up to 6 orders of magnitude and further observe that the EL on and off states can be either direct or inverted compared to the tunneling current on and off states. By comparing with the prewell containing sample, it is demonstrated that at room temperature the charge carriers confined at the prewell quantized state preserve the electrical current intensity with respect to the sample without prewell, therefore, it is thematically more stable. Finally, by studying the electroluminescence with magnetic field, it is demonstrated for the first time the Landau levels splitting in RTDs with emitter prewell.